Analisis faktor-faktor yang mempengaruhi ketepatan waktu pelaporan keuangan perusahaan perbankan yang terdaftar di Bursa Efek Indonesia Periode 2017-2019 - Yunicha Situmorang; Januardin Januardin (Program Studi Ekonomi Pembangunan Fakultas Ekonomi dan Bisnis Universitas Jambi, 2021)
This study analyzes the factors that affect the timeliness of submitting financial statements of banking companies listed on the Indonesia Stock Exchange in 2017-2019. Research data sourced from www.idx.co.id. Data were analyzed using multiple regression models. The study found that profitability, liquidity, and leverage significantly affected the timeliness of submitting financial statements. However, there is no evidence that ownership structure affects the timeliness of financial reporting..